Zinc Oxide-Based Q-Switched Erbium-Doped Fiber Laser *Supported by the University of Malaya under Grant No PG173-2015B. (March 2017) - Aziz, N. A.; Latiff, A. A.; Lokman, M. Q.; Hanafi, E.; Harun, S. W.
Abstract : We demonstrate a Q-switched erbium-doped fiber laser (EDFL) using a newly developed zinc oxide- (ZnO) based saturable absorber (SA). The SA is fabricated by embedding a prepared ZnO powder into a poly(vinyl alcohol) film. A small piece of the film is then sandwiched between two fiber ferrules and is incorporated in an EDFL cavity for generating a stable Q-switching pulse train. The EDFL operates at 1560.4 nm with a pump power threshold of 11.8 mW, a pulse repetition rate tunable from 22.79 to 61.43 kHz, and the smallest pulse width of 7.00 μs. The Q-switching pulse shows no spectral modulation with a peak-to-pedestal ratio of 62 dB indicating the high stability of the laser. These results show that the ZnO powder has a great potential to be used for pulsed laser applications.